Antioxidative, ACE inhibitory and antibacterial activities of soy milk fermented by indigenous strains of lactobacilli. Issue 4 (5th July 2020) - Singh, Brij Pal; Bhushan, Bharat; Vij, Shilpa
Abstract: Soy milk, a derivative of soybean, is an alternative to dairy beverage, but its acceptability is limited worldwide due to unpleasant beany flavour. Fermentation may, however, improve the nutritional and sensory values of soy milk. Thus, post‐fermentation improvement in functional attributes of soy milk were investigated via antioxidant, ACE inhibitory, and antimicrobial activities in this study using five test and one control strains of lactobacilli. Results indicated that soy milk fermented by Lactobacillus rhamnosus strain C25 (LR C25) effectively scavenged more than 60% of the ABTS, DPPH and Hydroxyl radicals generated in in vitro models. Moreover, all the strains showed significantly higher ( p < 0.05) antioxidant activity as compared to unfermented soy milk in all three assays performed. Further, Lactobacillus plantarum strain C6 (LP C6) fermented soy milk displayed significantly higher ( p < 0.05) percent ACE inhibitory activity (68.40 ± 0.93%) as compared to other tested Lactobacillus isolates, reference strain and unfermented soy milk. It was also observed that LP C6 strongly inhibited the growth of indicator strain of E. coli in the agar well diffusion assay. These strains can therefore be further explored in the preparation of beneficial soy foods and bioactive food supplements for wellbeing.